LOFGREN'S SYNDROME: CLINICAL CASE - A. E. Shklyaev; E. A. Semenovykh; L. V. Ivanova; A. N. Vedekhina (SINAPS LLC, 2019)
Sarcoidosis is an inflammatory disease characterized by the formation of non-caseating granulomas in various organs and tissues. The clinical signs of sarcoidosis are determined by the number of affected organs, the degree of their structural and functional impairment, and the severity of inflammatory symptoms. The article presents a clinical observation of one of the forms of sarcoidosis - Lofgren's syndrome, which is characterized by a triad of intrathoracic lymphadenopathy, acute arthritis and erythema nodosum. The diagnosis was confirmed histologically. Under the prescribed treatment, signs of acute inflammation reversed and the patient's state improved. The authors emphasize that they do not recommend widespread use of systemic glucocorticosteroids in patients with this disease, since their use may be associated with a relapsing course.